Hubungan Tingkat Pengetahuan Dengan Upaya Pengendalian Hipertensi Pada Lansia Di Puskesmas Kartasura - Adib Alfasyi, Khusnul; Sudaryanto, Agus (Universitas Duta Bangsa Surakarta, 2025)
Introduction: Hypertension is a circulatory disorder defined by blood pressure levels exceeding 140/90 mmHg. If not properly managed, hypertension can lead to severe complications, including stroke, heart disease, retinopathy, nerve disorders, kidney disease, and even death. Objectives: This study investigates the correlation between knowledge levels and efforts to manage hypertension among elderly individuals at the Kartasura Health Center. Methods: A quantitative approach was employed, utilizing a descriptive research design with a cross-sectional method. The study involved cluster sampling with 100 elderly hypertensive respondents at the Kartasura Health Center. Data analysis was conducted using the chi-square test.Results: The chi-square test yielded a p-value of 0.001 (p < 0.05), resulting in the rejection of H? and acceptance of H?. This confirms a significant relationship between knowledge levels and hypertension control efforts among the elderly at the Kartasura Health Center.Conclusions: The study concludes that there is a significant relationship between knowledge levels and hypertension management efforts among elderly individuals at the Kartasura Health Center